1984
DOI: 10.1038/312661a0
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic receptor stimulation activates enkephalin release and biosynthesis in adrenal chromaffin cells

Abstract: Neuroendocrine cells release a portion of their stored secretory hormone content when exposed to tissue-specific secretagogues. In the case of the adrenal medulla, catecholamines and enkephalin peptides, as well as other secretory proteins, are secreted in response to acetylcholine, which is released onto cholinergic receptors on chromaffin cells upon splanchnic nerve stimulation in vivo. Secretagogue stimulation thus depletes intracellular stores of exportable hormone. We were interested to know whether the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(72 citation statements)
references
References 9 publications
2
70
0
Order By: Relevance
“…These findings are consistent with neuronal release, and with increases in the synthesis and processing of proenkephalin A and prodynorphin-derived peptides. Their findings extend the earlier data of Eiden et al (1984). Subsequently, Davenport et al (1990) and Houdi et al (1991) demonstrated that nicotine caused the release of endogenous opioid peptides.…”
Section: Nicotine/tobacco Smoking and Brain Opioid Peptidessupporting
confidence: 85%
“…These findings are consistent with neuronal release, and with increases in the synthesis and processing of proenkephalin A and prodynorphin-derived peptides. Their findings extend the earlier data of Eiden et al (1984). Subsequently, Davenport et al (1990) and Houdi et al (1991) demonstrated that nicotine caused the release of endogenous opioid peptides.…”
Section: Nicotine/tobacco Smoking and Brain Opioid Peptidessupporting
confidence: 85%
“…First, the rate of synthesis can be modulated by protein kinase C alone as observed for CGA (23; this report). Secondly, synthesis can be regulated by both the elevation of cyclic AMP and the stimulation of protein kinase C as demonstrated here for CGB and previously reported for secretogranin I1 (14), enkephalin (26,36) and vasoactive intestinal polypeptide (37). In other words, the synthesis of secretory components appears to be regulated separately, allowing later, a second injection of 300 pg in incomplete Freund's adjuvant was given.…”
Section: Discussionmentioning
confidence: 85%
“…In chromaffin cells, the synthesis of various peptides, including enkephalin and vasoactive intestinal polypeptide, is regulated by cyclic A M P (26,27). We thus examined whether CGA and CGB synthesis might be affected by adenylate cyclase activators.…”
Section: Role Of Protein Kinase C In the Regulation Of Cga And Cgb Symentioning
confidence: 99%
“…Unlike neuropeptide genes which respond to secretagogue stimulation with increased gene transcription, or 'stimulus-secretion-synthesis coupling' [48], the CGA gene, as mentioned above, appears to be constitutively expressed upon secretagogue stimulation or depolarization of endocrine cells. Phorbol esters, at least in some cells, down-regulate CGA gene expression [25].…”
Section: Structure Of the Cga Gene And Regulation Of Cga Gene Transcrmentioning
confidence: 99%
“…Thus in contrast to CGA and CGB, SglI mRNA is up-regulated by depolarization of bovine chromaffin cells [50]. However, unlike mRNA encoding the neuropeptides enkephalin, NPY, galanin and CGRP [37,53,54] (Anouar and Eiden, in press, 1995), SglI mRNA is not up-regulated by insulin-induced trans-synaptic stimulation of the adrenal medulla in vivo [50], nor is it up-regulated by nicotinic stimulation as are chromaffin cell neuropeptides and their mRNAs [48,50]. Thus, SglI may represent an 'intermediate' between neuropeptide prohormone precursors, which are robustly up-regulated by secretory cell activity at the transcriptional level, and the constitutively expressed chromogranins A and B.…”
Section: Structure Of the Cga Gene And Regulation Of Cga Gene Transcrmentioning
confidence: 99%